A taste of home: an illustrated guide to Sarawak delicacies - Sebri, Nur Izzati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2025)
An Illustrated Guide to Sarawak Delicacies is a gift from food lover to food lovers. It was created to honour the spirit, capturing the taste of our land and the soul behind every meal. Each dish carries a whisper of heritage. The smoky aroma of Manok Pansoh recalls the warmth of longhouse fires. The fresh tang of Umai speaks of the sea and the fishermen who rise with the dawn. The beloved Sarawak Laksa, rich and fragrant, gathers all who taste it around the same table.